The Influence Length of Heating and Concentration of Giberelin on the Viability of Arabica Coffee Seeds (Coffea arabica L.) - Muhammad Sakti Harahap; Haryati Haryati; Ratna Rosanty Lahay (Jurnal Agroekoteknologi, 2018)
ABSTRACT The coffee germination process needed a relatively long time it because the coffee seed has a hard seed shell that is impermeable to water. To maximize the germination of coffee seeds need to be treated before planting. This research was conducted at Seed Technology Laboratory of the Agriculture Faculty, Universitas Sumatera Utara, Medan with height + 25 meter above sea level, from April to June 2017, using randomized block design with 2 factors of treatment. The first factor was the heating time with temperature 40°C with 4 levels i.e. 0, 5, 10 and 15 minutes, the second with gibberellin concentration with 4 levels i.e. 0, 250, 500 and 750 ppm. Parameter observed were growthpotential, germination rate, dead seed, vigor index, leaf appearance, hypocotyl length and root length. The results showed that the heating treatment had  no significant effect on all parameter observed. Gibberellin concentration significantly affected of growth potential, dead seed and vigor index. The interaction between heating time and gibberellin concentration had no significant effect on all parameter observed. Keywords: arabica coffee seed, gibberellin, length of heating, viability